(untitled) (World Bulletin of Social Sciences, 2026)
The article presents a systemic methodological analysis of interactive teaching as an integral pedagogical model in teaching Russian as a foreign language to university students who graduated from national schools. Unlike fragmentary use of interactive techniques, the study conceptualizes interactive methodology as a structured pedagogical system aimed at overcoming linguistic barriers and ensuring communicative adaptation in a multilingual academic environment. The research is grounded in communicative linguodidactics, constructivist theory, and activity-based pedagogy. The article proposes a model of interactive instruction that integrates psychological support, collaborative learning, and formative assessment as core components of effective foreign language acquisition.